PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA DENGAN MODEL KOOPERATIF TIPE INDEX CARD MATCH BERBANTUAN CANVA DI KELAS V UPT SDN 05 MUARA KANDIS: Penelitian Tindakan Kelas - Andriani, Diva; Wahyuni, Etri; Anita, Yesi; Muhammadi, Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning outcomes in Pancasila Education at the elementary school level remain relatively low due to teacher-centered instruction, limited use of learning media, and the lack of innovative learning models that actively engage students. This study aimed to improve students' learning outcomes in Pancasila Education through the implementation of the Cooperative Learning Model of the Index Card Match (ICM) type assisted by Canva. This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The study was conducted in two cycles involving 20 fifth-grade students of UPT SDN 05 Muara Kandis. Data were collected through observation, learning achievement tests, and documentation, then analyzed using descriptive qualitative and quantitative techniques. The findings indicated that the implementation of the Index Card Match cooperative learning model assisted by Canva improved the quality of lesson planning, classroom implementation, and students' learning outcomes. The lesson module assessment increased from 93.72% in Cycle I to 95.83% in Cycle II. Teacher activities improved from 87.50% to 93.18%, while students' learning activities increased from 88.00% to 93.18%. Students' average learning outcomes also improved from 72.47 in the first meeting of Cycle I to 80.75 in the second meeting and reached 83.77 in Cycle II with a classical mastery percentage of 90%. Therefore, the Canva-assisted Index Card Match cooperative learning model effectively improves learning outcomes in Pancasila Education for fifth-grade elementary school students.